GE_GERICHTE P/24832/2021 vom 31. Juli 2023 - GE Cour de justice (2023)
AGGRAVATION DE LA PEINE | LD.118.al1; LD.118.al3; LAlc.54.al2; OVA.96.al1; LIB.35.al1; LIB.35.al2.letb; DPA.9; CP.48.lete; CP.66a.al1.letf